Local Invisibility, Postcolonial Feminisms Asian American Contemporary Artists in California - Fantone, Laura (Critical Studies in Gender, Sexuality, and Culture, 2018)
This book offers gendered, postcolonial insights into the poetic and artistic work of four generations of female Asian American artists in the San Francisco Bay Area. Nancy Hom, Betty Kano, Flo Oy Wong, Trinh T. Minh-ha, Theresa H.K. Cha, and Hung Liu are discussed in relation to the cultural politics of their time, and their art is examined in light of the question of what it means to be an Asian American artist. Laura Fantone's exploration of this dynamic, understudied artistic community begets a sensitive and timely reflection on the state of Asian American women in the USA and in Californian cultural institutions.